Does total volume of physical activity matter more than pattern for onset of CVD? A prospective cohort study of older British men. (1st March 2019) - Jefferis, Barbara J.; Parsons, Tessa J.; Sartini, Claudio; Ash, Sarah; Lennon, Lucy T.; Papacosta, Olia; Morris, Richard W.; Wannamethee, S. Goya; Lee, I-Min; Whincup, Peter H.
Abstract: Aims: With increasing age, physical inactivity and sedentary behaviour levels increase, as does cardiovascular disease (CVD) incidence. We investigate how device-measured sedentary behaviour and physical activity (PA) are related to CVD onset in men aged 70+; whether the total volume of activity is more important than pattern. Methods and results: Prospective population-based cohort study of men recruited from 24 UK General Practices in 1978–80. In 2010–12, 3137 survivors were invited to complete questionnaires and wear an Actigraph GT3x accelerometer for 7 days. PA intensity was categorised as sedentary, light and moderate to vigorous (MVPA). Men were followed up for Myocardial Infarction, stroke and heart failure (ICD9 410–414, 430–438 and 428) morbidity and mortality from 2010 to 12 to June 2016. Hazard Ratios (HRs) for incident Cardiovascular Disease (CVD) were estimated. 1528/3137 (49%) men had sufficient accelerometer data. 254 men with pre-existing CVD were excluded. Participants' mean age was 78.4 (range 71–92) years. After median 4.9 years follow-up, 122 first CVD events occurred in 1181 men (22.7/1000 person-years) with complete data. For each additional 30 min in sedentary behaviour, light PA, 10 min in MVPA, or 1000 steps/day, HRs for CVD were 1.09(95%CI 1.00, 1.19), 0.94(0.85, 1.04), 0.88(0.81, 0.96) and 0.86(0.78 to 0.95) respectively, adjusted for measurement-related factors, socio-demographics, health behaviours and disability. HRs for accumulating 150 min/week MVPA in bouts ≥1 min and bouts ≥10 min were 0.47(0.32 to 0.69), and 0.49(0.25, 0.98). Conclusions: In older men, high volume of steps or MVPA rather than MVPA bouts was associated with reduced CVD risk. Highlights: Prospective studies report that self-reported physical activity protects against cardiovascular disease (CVD). Yet, self-reported behaviours cannot easily be used to assess the value of the 10 min activity bouts specified in guidelines. This is the first study of risk of fatal and non-fatal CVD based on device measured physical activity and sedentary behaviour. Among 1181 men aged over 70 years, more time in moderate to vigorous physical activity and more steps reduced 5-year CVD risk. The pattern of accumulating moderate to vigorous physical activity in 10 min bouts was not important for CVD risk.